Literature review of current research topics in fluid mechanics of turbomachinery and preliminary design of a test rig - Andrew Gerard Jayamaha (2017)
This report presents a comprehensive look at the available literature in the field of fluid mechanics and turbomachinery. Various trends, both past and present, are presented, analysed and examined to determine their usefulness in future turbomachinery designs and processes. Key areas for future development are also highlighted. An examination is made on the available literature for calculation and performance prediction methodology currently used in turbomachinery design. Methods such as the matrix through flow and streamline curvature method are described and modifications suggested to improve accuracy. The influence of unconventional working fluids on turbomachinery performance is also scrutinised utilising the limited literature currently available. Suggestions are also made regarding proposed modifications to existing commercial software to better accommodate unconventional working fluids. Various turbomachinery design conditions including interaction between the fluid and the machinery itself, predictions for fluid phase transition as well as the use of various optimisation techniques and calculations is investigated. This report also discusses in detail the various CFD techniques and software commonly used in turbomachinery design and performance analysis. A proposal for a new test rig design that allows both simultaneous and isolated testing of two promising trends in turbomachinery design is presented. The first is the use of unconventional working fluids which holds promise in improving turbomachine performance and efficiency and the second is the effect of unsteady flow at the turbomachine inlet. Both are areas that are currently lacking in research and yet the little research that does currently exist shows real promise. Additional proposals are also made for the development of a new type of CFD software which is able to accurately model the effects of unsteady flow at the turbomachinery inlet while also being able to link to a separate database containing the fluid properties of a range of conventional and unconventional working fluids.